2016
DOI: 10.1002/2016gc006369
|View full text |Cite
|
Sign up to set email alerts
|

Density and P‐wave velocity structure beneath the Paraná Magmatic Province: Refertilization of an ancient lithospheric mantle

Abstract: We estimate density and P‐wave velocity perturbations in the mantle beneath the southeastern South America plate from geoid anomalies and P‐wave traveltime residuals to constrain the structure of the lithosphere underneath the Paraná Magmatic Province (PMP) and conterminous geological provinces. Our analysis shows a consistent correlation between density and velocity anomalies. The P‐wave speed and density are 1% and 15 kg/m3 lower, respectively, in the upper mantle under the Late Cretaceous to Cenozoic alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
4

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 99 publications
(167 reference statements)
4
41
0
4
Order By: Relevance
“…Both basins had very similar evolution with the first subsidence stage in the Paleozoic, and both had a significant magmatic event in the Mesozoic, producing large volumes of flood basalts. This difference in crustal thickness may be compensated by differences in the upper mantle, such as a thick lithospheric lid beneath the Paraná Basin with high velocities (Feng et al, ; Schaeffer & Lebedev, ; Rocha et al, ) and high density (Chaves et al, ), whereas beneath the Parnaíba Basin high Pn velocities were found only along a small 400‐ to 500‐km section in its center (Soares et al, ). This may imply that the cratonic block beneath the Parnaíba Basin is smaller and thinner compared with that of the Paraná Basin in the south.…”
Section: Resultsmentioning
confidence: 99%
“…Both basins had very similar evolution with the first subsidence stage in the Paleozoic, and both had a significant magmatic event in the Mesozoic, producing large volumes of flood basalts. This difference in crustal thickness may be compensated by differences in the upper mantle, such as a thick lithospheric lid beneath the Paraná Basin with high velocities (Feng et al, ; Schaeffer & Lebedev, ; Rocha et al, ) and high density (Chaves et al, ), whereas beneath the Parnaíba Basin high Pn velocities were found only along a small 400‐ to 500‐km section in its center (Soares et al, ). This may imply that the cratonic block beneath the Parnaíba Basin is smaller and thinner compared with that of the Paraná Basin in the south.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that in the northern and central parts of the Parana magmatic province, where the thickest and largest volume of basalts were emplaced, lithospheric mantle down to 250-300 km is characterized by high-velocity perturbation (> 0.5 %) and high-density contrast (> 30 kg/m3). According to Chaves et al (2015) these results, when correlated with a geoeletrical model obtained by deep electromagnetic induction studies (GDS), which exhibits low-resistivity in relation to typical values obtained in cratons, preclude the idea of a cratonic block (Paranapanema) beneath the central Parana magmatic province. …”
Section: The South Atlantic Magmatic Provincementioning
confidence: 91%
“…Individual plumes such as Tristan da Cunha, along the eastern margin of the African large low shear velocity province (llsvp) (White & McKenzie, 1995;Torsvik, 2006Torsvik, , 2009) and decompression melting farther to the south (Gladczenko et al, 1997;Blaich et al, 2011;Stica et al, 2013) each played some role in this progressive breakup of Pangea from Triassic time. Chaves et al (2015) suggested delamination of the continental lithosphere; according to these authors, lowering of melting temperature may be caused by the presence of metasomatic fluids in the delaminated or detached continental lithosphere. A major pulse of heat flow from the Earth's core is suggested by the near-antipodal position of the SAMP to the early Cretaceous Ontong-Java Plateau in the Pacific.…”
Section: The South Atlantic Magmatic Provincementioning
confidence: 97%
See 1 more Smart Citation
“…The same authors points to notable isotopic differences between the PEMP basalts and ocean islands along the Tristan da Cunha track, indicating a minor role of the plume. Recent geophysical investigation points to a high-density lithosphere underlying the PMP, attributed to a highly altered and fertile lithosphere (Chaves et al, 2016).…”
Section: Continental Flood Basalts: a Brief Review And Insights Into mentioning
confidence: 99%